2023
DOI: 10.1037/dev0001504
|View full text |Cite
|
Sign up to set email alerts
|

Boys and girls, men and women: Do children take stimulus age into account when expressing gender stereotypes?

Abstract: Gender and age are salient social categories from early in development. However, whether children's beliefs about gender and age intersect, such that gender stereotypes might be expressed differently when asked about children (compared to adults) has not been investigated. Here, in a preregistered study (N = 297), we examined if young children (3.0-6.9-year-olds, M age = 5.03 years, n = 145) and adults (n = 152) across Massachusetts were more likely to express gender stereotypes when presented with child or ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…An analysis using only the story or the guessing task revealed similar patterns (see Table S3). An additional analysis using a linear mixed model including the age of target (adult versus child) revealed no significant main effect or interactions involving target age, ps > .136, confirming previous findings that children hold similar gender stereotypes when judging adults and children (Alto & Mandalaywala, 2023;Bian et al, 2017).…”
Section: Resultssupporting
confidence: 80%
“…An analysis using only the story or the guessing task revealed similar patterns (see Table S3). An additional analysis using a linear mixed model including the age of target (adult versus child) revealed no significant main effect or interactions involving target age, ps > .136, confirming previous findings that children hold similar gender stereotypes when judging adults and children (Alto & Mandalaywala, 2023;Bian et al, 2017).…”
Section: Resultssupporting
confidence: 80%
“…An analysis using only the story or the guessing task revealed similar patterns (Table S3). An additional analysis using a linear mixed model including the age of target (adult vs. child) revealed no significant main effect or interactions involving target age, ps > .136, confirming previous findings that children hold similar gender stereotypes when judging adults and children (Alto & Mandalaywala, 2023;Bian et al, 2017).…”
Section: Gender Stereotype About Brilliancesupporting
confidence: 81%
“…Past studies have found that when high status is not framed in terms of power but in terms of leadership, Western children do not necessarily link it to gender [ 89 ]. Moreover, when asking adults about children's gendered traits [ 90 , 91 ], ‘leader’ does not emerge as a stereotype of boys, whereas ‘dominant’ (e.g. aggressive) does.…”
Section: Discussionmentioning
confidence: 99%